The Influence of Motivation on Employee Performance of Trade and Industrial Department of Gowa Regency - Tawe, Amiruddin; Musa, Chalid Imran (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of motivation on employee performance at the Department of Trade and Industry of Gowa Regency. The population in this study were all employees at the Department of Trade and Industry of Gowa Regency, totaling 40 people. The number of samples used is the entire population because there are less than 100 people, namely the type of saturated cover, with this type of quantitative research. The data used are primary data and secondary data obtained using a questionnaire distribution technique. The results of the research after being processed with SPSS.21 Based on the results of the research it shows that motivation (X) has a coefficient value of 0.841 and t_count > t_table (3.385 > 2.026) and the value of Sig. of 0.002 <0.05, which means that motivation has a positive and significant effect on employee performance.